Removal of Copper (II) Ions in Aqueous Solutions by Sorption onto Fly Ash - Darmayanti, Lita; Notodarmodjo, Suprihanto; Damanhuri, Enri (Journal of Engineering and Technological Sciences, 2017)
The ability of fly ash to adsorp Cu(II) ions from two different coal combustion systems was studied. Optimum removal was found at pH 5, contact time 30 minutes and 60 minutes for Fly Ash 1 and Fly Ash 2, respectively, and dosage 10 g/l. The difference in adsorption capacity between both fly ashes may be due to their carbon fraction and CaO content. The removal of Cu (II) ions was caused by both adsorption and/or precipitation. Precipitation is enhanced by lowering the carbon fraction and increasing the CaO content. The adsorption isotherm showed that the Langmuir model fitted well to the experimental data of both fly ashes. A thermodynamic study was conducted at three different temperatures: 25 °C, 45 °C, and 60 °C. The adsorption processes were spontaneous and endothermic and were more favorable at higher temperature.